A baseline patch test series for New Zealand. (22nd July 2021) - Seine, Adrian J; Baird, Elizabeth Ann; Chan, Lydia; Davis, Anne; Greig, Deborah; Judd, Lissa Elaine; Mahon, Caroline; Oakley, Amanda; Rademaker, Marius; Reiche, Louise; Stanway, Amy Donna; Cheng, Harriet S
Abstract: Background: Patch testing is the gold standard diagnostic test for allergic contact dermatitis and needs to be relevant to the region and the population being tested. The aim of this study was to develop a specific New Zealand baseline series (NZBS). Method: We performed a retrospective case note review of patients attending four regional patch test centres between 2008 and 2020. Demographic and diagnostic information was collected for each patient along with results of patch testing. Using the results of this review, a group of 11 dermatologists with an interest in contact dermatitis agreed on a core group of allergens for inclusion in an NZBS, based on the frequency of positive reactions and allergens of interest. The remaining potential allergens were ranked by each dermatologist using an online questionnaire, with inclusion in the final NZBS by consensus. Results: Results from 2402 patients (67% female, mean age 44 years) from Auckland, Wellington, Palmerston North and Christchurch were collated. The 10 most frequent positive (relevant and non‐relevant) allergens were nickel sulfate (22.0%), fragrance mix I (8.6%), cobalt chloride (7.3%), Myroxylon pereirae (5.6%), colophonium (5.1%), p ‐phenylenediamine (4.9%), methylisothiazolinone/methylchloroisothiazolinone (4.1%), fragrance mix II (3.9%), potassium dichromate (3.5%) and methylisothiazolinone (3.4%). Based on these results, a core series of 30 allergens was developed, with an additional 30 allergens added to form the extended series (total 60 allergens). Conclusion: The baseline series of patch test allergens for routine use in New Zealand (NZBS) is based on national patch test data and expert consensus.